Gender Differences in Social Comparison Processes and Self-Concept Among Students - Valls, Marjorie (Frontiers in Education, 2022)
Forced social comparison (i.e., comparing oneself to another “predefined” student) has often been studied in school settings. However, to our knowledge, studies that explore its association with academic self-concept have rarely distinguished between subjects involved (e.g., mathematics or language learning). Moreover, some processes taking place during forced social comparison are thought to have a negative impact on academic self-concept. Thus, the aims of this study were to explore: 1) the associations between self-concepts (i.e., Language learning, Mathematics and Social), attitudes towards school and social comparison processes in school settings; and 2) the influence of social comparison processes on components of academic self-concept across gender. A sample of 238 elementary school students (Mage= 10.12, SD= 1.25; 52% boys) completed a questionnaire assessing self-concepts and attitudes towards school, as well as a questionnaire measuring four social comparison processes. Results indicated that girls used negative processes (i.e., upward contrast and downward identification) more than boys. In addition, boys reported better self-concept in mathematics while girls reported better self-concept in language learning (small effect). Results of stepwise multiple linear regression analyses showed that upward contrast best explained gender differences, with a stronger effect for girls. Attitudes towards school only explained gender differences in language learning self-concept. Furthermore, positive processes (i.e., upward identification and downward contrast) have no effect on either component of academic self-concept. Results of this study demonstrate the need to examine the evolution of social comparison processes over time, considering their impact on students’ academic/social well-being and achievement from a gender perspective.